Sõjakoorem. Kolmekümneaastase sõja ajal Prantsuse ordonnantsidega esitatud sõjalised nõudmised tsiviilelanikele [The burdens of war. Military demands on the civil populationin French ordinances during the Thirty Years` War] - Forssberg, Anna Maria (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2012)
War has always been considered the responsibility of the ruler, but it has vastly affected the common people. This article investigates the wartime relationship between king and subjects through royal ordinances published in France in the beginning of the Thirty Years War. The aim is to find out whether there is a distinction between a military and civilian sector in the sources and, furthermore, to investigate how the reasons forwar and the responsibility for war were described. (Longer version of the current abstract is included in the article, starting from p 54.)